Effect of parameters on the cost of memory type chart / Sakthiseswari Ganasan, You Huay Woon and Zainol Mustafa - Ganasan, Sakthiseswari; You, Huay Woon; Mustafa, Zainol (2021)
A memory type control chart is a scheme that utilizes previous information for constructing the chart. An exponentially weighted moving average (EWMA) control chart is an example of a memory type chart. The EWMA control chart is well-known and widely employed by practitioners for monitoring small and moderate process mean shifts. In light of this, the cost of implementing an EWMA control chart needs to be determined. This study aims to investigate the effect of input parameters on the cost of implementing an EWMA control chart. Here, the economic model was used to compute the cost parameter. The 14 input parameters were identified and the analysis was carried out based on the one-parameter-at-a-time basis. When the input parameters change based on a predetermined percentage, the cost is also affected. According to the results, 10 input parameters with major effect and 4 input parameters with almost no effect on the cost parameter. However, the effect of each input parameter on the cost is different. This analysis is crucial to observe and determine the input parameters that have a significant impact on the cost of the EMWA control chart. Hence, practitioners can obtain an overview of the influence of the input parameters on the cost of implementing the EWMA control chart.